Pengembangan Dan Peningkatan Usaha Produk Olahan Bandeng Di Kecamatan Pakal Surabaya - indri astuti (Asian Journal of Innovation and Entrepreneurship, 2018)
Milkfish (Chanos chanos) is a popular food fish in Southeast Asia. This fish is the only species still present in the Chanidae. In Surabaya, the demand for processed milkfish products is quite large. The community's trend to eat milkfish is very profitable for the producers. In Pakal Sub-district Surabaya, there are 2 (two) Self-Help Groups (KSM) which have business of Processed Milk Products: 1) Members  of Self-Help Group (KSM) namely Gelora Bandeng RT 01 RW06 Wonorejo Sub-District Pakal Surabaya as partner 1 and  2) members of Self-Help Group (KSM) namely Bandeng Bara In Pondok Benowo Indah  RT01 RW 09 Kelurahan Babat Jerawat Kecamatan Pakal Surabaya as Partner 2.  Both Partner 1 and 2 encountered the same probles that can be divided into Management problems and production problems.  In management problems are Lack of working capital, Less orderly administration.   From Production matter there are some problems related to the needs to training variants of processed milkfish products, Food Processor needs larger capacity, less attractive packaging, and partner 2 does not have Certificate of Household Food Production, anad there is no name board in their  production house. The solution offered from the management side is to provide information about utilizing existing capital effectively and Efficiency, developing and applying blog or other online marketing medias, applying  IT based-administration particularly  using Microsoft Office Excel in simple bookkeeping.  From the production side we conducted training to develop product variants, showing how to make Brand through a simple tutorial over the Internet., help to gain PIRT  Certificate for partner 2,  giving production equipment such as larger capacity Food Processor, and the construction of name board for the Production House.